Skrining Bakteri Asam Laktat Penghasil Bakteriosin dari Daging dan Produk Olahannya - Endang Sri Rahayu; A.K. Wardani; S. Margino (agriTECH, 2004)
Lactic acid bacteria (LAB) which naturally occur in meat and meat products have been isolated and screened for their ability to produce bacteriocin. The objective of this research was to obtain the potential bacteriocin producer of lactic acid bacteria which could be used as food bio-preservative. Source of lactic acid bacteria used in this study were beef chicken flesh, 'vacuum packaged' sausage and sliced meat obtained from traditional market or department store. Ten grams of each samples was put onto five different enrichment media, i.e., TGE (tryptoneglucose-yeast extract) pH 5 plus 3% NaCl; MRS (deMan Rogose Sharpe) pH 5,5; TGE broth pH 5,5; TGE buffer broth pH 5,5; and TGE broth plus Tween 80 & 1% Naazida pH 6,0, incubated for 24-71 hours to stimulate the growth of lactic acid bacteria. Different enrichment media were used to stimulate the growth of strains belong to each genus, since the nutritional and environmental requirement for optimum growth were suggested to be genera-dependent. Screening of LAB bacteriocin producer was carried out by dilution -pour plate methods (culture from each enrichment medium) followed by overlay using the indicator strains. Indicator strains used in this study were Lactobacillus plantarum NCDO 955, Pediococcus acidilactici LB-42, Leuconostoc mesenteroides LY, and Enterococcus faecalis MI. Colonies showing growth inhibition to indicator (indicated by clear zone) were isolated and purified. Isolates were then characterized based on Gram, catalase, shape and arrangement of cell, type of fermentation, effect of temperature to the growth and acid production from several carbon sources. From the primary screening (dilution - pour plate –overlay), 30 strains belong to Lactobacillus, Leuconostoc, Streptococcus and Enterococcus which suspected to produce antimicrobial substance were obtained. However, based on the confirmation lest (dUsion method), only three (3) strains were identified to produce bacteriocin. i. e. Leuconostoc mesenteroides SM 22, SM 32, and SM 46. In this study, Leuconostoc mesenteroides SM 22 was selected for food application. Bacteriocin of Leuconostoc mesenteroides SM-22 was able to inhibit the growth of psychrophilic bacteria naturally occur in meat and shrimp kept at refrigerator. Microbial population of raw meal with the initial number of about 3x104 CFU/g decreased one log cycle after treated with bacteriocin, and this number maintained less than 105 CFU/g after storage raw meat at refrigerator for five days. On the other side, microbial population of raw meat with no bacteriocin treatment increased to 106 CFU/g after 4 days kept at refrigerator. In the case of shrimp, washing raw shrimp with cold water could reduce the population of bacteria about one log cycle, followed treatment with bacteriocin, this populationincreased very slowly and still less than 105 CFU/g after 5 days storage at refrigerator. While without any treatment, microbial population of raw shrimp which initially about 3x105 CFU/g rapidly increased to 106 CFU/g after 3 days. This data showed that Leuconostoc mesenteroides SM-22 was a potential bacteriosin producer and can be applied as bio-preservative for cold storage fbod.